Community-based co-design of a crowdsourcing task management application for safeguarding indigenous knowledge - Stanley, Colin (Department of Computer Science, 2021)
Teaching indigenous knowledge (IK) to African youth has become more complicated due to a variety of reasons such as urban migration, loss of interest in it, the dominance of scientific knowledge and the technological revolution. Therefore, there is a considerable movement towards using technologies to safeguard IK before it becomes obsolete. It is noteworthy that research conducted and software development perspectives being used are mainly based on Western worldviews that are inappropriate for African socio-cultural contexts. IK holders are often not in charge of the digitisation process and merely treated as subjects. In this study, we explored a suitable development approach of a crowdsourcing task management application (TMA) as an auxiliary tool for safeguarding IK. Moreover, the study sought to provide an opportunity for the indigenous communities to make requests of three-dimensional (3D) models of their traditional objects independently. The delivered traditional 3D models are imported into the communities' IK visualisation tools used by the IK holders to teach the youth about their cultural heritage. The main objective of this study was to ascertain how the indigenous rural communities could appropriate a foreign technological concept such as crowdsourcing. This brought about our first research theme: investigating the necessary conditions to establish and maintain beneficial embedded community engagement. The second theme was to determine the suitable methods for technology co-design. Thirdly, to discover what does the communities' appropriated crowdsourcing concept entail. We applied a consolidated research method based on Community-based CoDesign (CBCD) extended with Afrocentric research insights and operationalised with Action Research cycle principles of planning, action and reflection. CBCD was conducted in three cycles with Otjiherero speaking indigenous rural communities from Namibia. Reflections from the first cycle revealed that the rural communities would require unique features in their crowdsourcing application. During the second cycle of co-designing with the ovaHimba community, we learnt that CBCD is matured through mutual trust, reciprocity and skills transfer and deconstructing mainstream technologies to spark co-design ideas. Lastly, in our third cycle of CBCD, we showcased that communities of similar cultures and knowledge construction had common ideas of co-designing the TMA. We also simulated that the construction of traditional 3D models requires indigenous communities to provide insight details of the traditional object to minimise unsatisfactory deliverables. The findings of this study are contributing in two areas (1) research approach and (2) appropriation of technology. We provide a synthesis of Oundu moral values and Afrocentricity as a foundation for conducting Afrocentric research to establish and maintain humanness before CBCD can take place. With those taken as inherent moral values, Afrocentricity should then solely be focused on knowledge construction within an African epistemology. For the appropriation of technology, we share codesign techniques on how the indigenous rural communities appropriated the mainstream crowdsourcing concept through local meaning-making. CBCD researchers should incorporate Afrocentricity for mutual learning, knowledge construction, and sharing for the benefit of all.